2020
DOI: 10.20473/bikk.v32.2.2020.119-125
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Lipid Profile and Xanthelasma

Abstract: Background: Xanthelasma is an abnormal lipid deposition on palpebrae, which is observable as yellowish plaque or nodules. Its incidence is 0.56–1.5% with onset of 15–73 years old and mostly occurs in the fourth and fifth decade. Few reports of xanthelasma did not cover the correlation between lipid profile and xanthelasma in Indonesia. Purpose: To find a correlation between lipid profile with xanthelasma in Dr. M. Djamil Hospital, Padang. Methods: This was an analytic cross-sectional study with consecutive sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
2
5
1
Order By: Relevance
“… 4 Published literature had shown that the group with the highest prevalence of xanthelasma was 41-50 years old (38.89%). 8 This finding was contrary to our study in which the highest number of cases (26.56%) were in the age group 46-55 years.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“… 4 Published literature had shown that the group with the highest prevalence of xanthelasma was 41-50 years old (38.89%). 8 This finding was contrary to our study in which the highest number of cases (26.56%) were in the age group 46-55 years.…”
Section: Discussioncontrasting
confidence: 83%
“…In a reported study, the mean ages of the patient were 47.4±9.97 years and in most patients (69%) duration of xanthelasma lesions was less than one year, 2 where as in another study the mean age of the patients was 48.61±12.36 years old and mean onset was 48.11±12.27 years. 8 In the same way, in our study the mean ages of the patients was 53.28±14.61 years and 57.81% patient with xanthelasma lesions had duration six months to one year.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations